The Use of Digital Media in Increasing Student Learning Motivation in the Subject of Creed and Ethics at Al Khoiriyah Patihan Elementary School - Yuniatun; Yulistyaningsih; Yuliati; Yumna; Wardani, Yuyun (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to determine the effectiveness of using digital media in increasing students' learning motivation in the subject of Akidah Akhlak at MI Al Khoiriyah Patihan. The background of this study is based on the low learning motivation of students as seen from the lack of active participation in the learning process and the lack of interest in understanding the material of Akidah Akhlak. To overcome these problems, this study applies digital media as a learning aid to increase student involvement and motivation. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. The subjects of the study were grade V students of MI Al Khoiriyah Patihan. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The data obtained were analyzed descriptively quantitatively and qualitatively to see changes in students' learning motivation after the application of digital media. The results of the study showed that the use of digital media, such as learning videos, interactive presentations, and educational applications, was able to significantly increase students' learning motivation. This is indicated by the increasing activeness of students in learning, their enthusiasm in following the material, and the improvement in learning evaluation results. In the first cycle, the percentage of students who showed high motivation reached 65%, and increased to 85% in the second cycle. The conclusion of this study is that the use of digital media can be an effective solution in increasing students' learning motivation in the subject of Akidah Akhlak. With the application of digital media, learning becomes more interesting, interactive, and enjoyable for students. Therefore, teachers are expected to be able to integrate technology in learning to create a more dynamic learning atmosphere and support increased student learning motivation